Gene Polymorphisms Associated with Central Precocious Puberty and Hormone Levels in Chinese Girls - Yunwei Li; Na Tao; Minghui Chen; Jiang Chu; Xinwei Huang; Xiangyang Kong (International Journal of Endocrinology)
Central precocious puberty (CPP) is associated with adverse health outcomes in females; however, CPP pathogenesis remains unclear. In this study, we investigated the association of 20 single nucleotide polymorphisms (SNPs) in eight genes with CPP risk and hormone levels. A case-control study on 247 and 243 girls with and without CPP, respectively, was conducted at Kunming Children’s Hospital, China, from September 2019 to August 2020. The genotype of the SNPs and their haplotypes were identified. Additionally, the effects of the polymorphisms on hormone levels were investigated. Three variants (rs10159082, rs7538038, and rs5780218) in KISS1 and two variants (rs7895833 and rs3758391) in SIRT1 were related to an increased CPP risk (odds ratio (OR) = 1.524, 1.507, 1.409, 1.348, and 1.737; 95% confidence interval (CI) = 1.176–1.974, 1.152–1.970, 1.089–1.824, 1.023–1.777, and 1.242–2.430, respectively). Rs3740051in SIRT1 and rs1544410 in VDR reduced CPP risk (OR = 0.689, 0.464; 95% CI, 0.511–0.928, 0.232–0.925, respectively). Rs1544410, rs7975232, and rs731236 in VDR were negatively correlated with peak follicle-stimulating hormone (FSH; β = −2.181; P=0.045), basal FSH (β = −0.391; P=0.010), and insulin-like growth factor (β = −50.360; P=0.041) levels, respectively. KISS1, SIRT1, and VDR variants were associated with CPP susceptibility, and VDR SNPs influenced hormonal levels in Chinese females with CPP. In particular, VDR polymorphism rs1544410 was associated with both CPP risk and GnRH-stimulated peak FSH levels. Further functional research and large-scale genetic studies of these loci and genes are required to confirm our findings.